2017
DOI: 10.1089/ars.2016.6904
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Local and Systemic Heterocellular Communication by Mechanical Forces: A Role of Endothelial Nitric Oxide Synthase

Abstract: Significance: In this review, we discuss the role of nitric oxide (NO) as a key physiological mechanotransducer modulating both local and systemic heterocellular communication and contributing to the integrated (patho)physiology of the cardiovascular system. A deeper understanding of mechanotransduction-mediated local and systemic nodes controlling heterocellular communication between the endothelium, blood cells, and other cell types (e.g., cardiomyocytes) may suggest novel therapeutic strategies for endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 161 publications
(247 reference statements)
0
25
0
1
Order By: Relevance
“…In fact, it had already been shown that the production of NO increases in proportion to the intensity of physical exercise until exhaustion and that regular training induces an increase in the concentration of salivary NO [25]. Endothelial NO synthase production in vascular endothelial cells is a result of higher blood flow to the active tissue [26]. For this reason, we hypothesize that the increase in blood flow in athletes during exercise is an important factor stimulating NO production in the vessels; however, we did not measure blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it had already been shown that the production of NO increases in proportion to the intensity of physical exercise until exhaustion and that regular training induces an increase in the concentration of salivary NO [25]. Endothelial NO synthase production in vascular endothelial cells is a result of higher blood flow to the active tissue [26]. For this reason, we hypothesize that the increase in blood flow in athletes during exercise is an important factor stimulating NO production in the vessels; however, we did not measure blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function is improved with exercise even in the absence of changes in classical risk factors like lipids levels, blood pressure, glucose or BMI (Green et al 2008). Acute-and moderate-intensity exercises increase shear stress, which stimulates endothelium-dependent vasodilatation through the increased synthesis of nitric oxide (Erkens et al 2017). Regular exercise training also leads to increased coronary artery size and dilatation capacity (Haskell et al 1993) and increased luminal diameter of conduit arteries (Green et al 2008).…”
Section: Physical Activitymentioning
confidence: 99%
“…NO participates in regulating vascular tone, blood perfusion, and adaptive response to shear forces . Disruption of NO may impair organ perfusion and thereafter induce tissue ischemia .…”
Section: Introductionmentioning
confidence: 99%